Article with thermoset coating and coating method
Through the combination of thermoset coating and lubricant, the galvanic corrosion problem is solved, ensuring the stability and mechanical properties of the material in the electrolyte environment, and is suitable for high temperature conditions.
Patent Information
- Application Number
- CN202411462007.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-02-02
- Filing Date
- 2016-02-03
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively prevent galvanic corrosion, especially when different materials are in contact in the presence of electrolytes, and traditional coatings may affect mechanical properties or increase costs.
A thermoset coating, especially a crosslinked epoxy resin coating, is employed, by powder spraying and curing under an induction heater, combined with a lubricant coating, to form a stable barrier at high temperatures to prevent galvanic corrosion.
The galvanic corrosion protection between different materials in the presence of electrolyte is achieved, the mechanical properties of the system are maintained, and durability and cost-effective under high temperatures and repeated heating and cooling conditions are shown.
Smart Images

Figure CN119114391A_ABST
Abstract
Description
[0001] Cross-references to related application materials
[0002] This application claims priority to U.S. Provisional Patent Application No. 62111495, filed on February 3, 2015, and U.S. Provisional Patent Application No. 62257015, filed on November 18, 2015, the disclosures of which are incorporated herein in their entirety. Technical Field
[0003] Certain aspects of the present invention relate to articles and / or assemblies having coating compositions or characteristics, and to methods for coating such articles. In particular, certain aspects of the present invention relate to a metal article at least partially coated with one or more thermosetting coatings and / or inorganic coatings that are capable of preventing galvanic corrosion when the article is in contact with a dissimilar metal or other material in the presence of an electrolyte, assemblies having such articles, and methods for producing such articles. Background Art
[0004] There are many different types of corrosion. Generally speaking, corrosion is the process of converting a material (such as a metal) into a more stable form. However, there are two main types of corrosion: general or uniform corrosion; and galvanic corrosion. For example, general or uniform corrosion can occur when iron is in a wet or humid environment, and the iron corrodes, forming iron oxide in the process.
[0005] On the other hand, galvanic corrosion occurs when two materials with different anodic indices or potentials are in contact or close to each other in the presence of an electrolyte. The potential difference creates a flow of electrons between the materials. In such a system, one of the materials is more active (or has a lower potential) and acts as an anode, while the other material is less active (or has a higher potential) and acts as a cathode. The anode corrodes at a faster rate, while the cathode corrodes at a slower rate.
[0006] An example of a system where galvanic corrosion can occur is a steel bolt securing a magnesium plate to an object in the presence of non-distilled water, such as in a salt spray environment. The magnesium, being at a lower potential than the steel, will corrode at a faster rate, while the steel will corrode at a slower rate. This problem is not limited to dissimilar metals, where galvanic corrosion can occur, for example, when steel bolts are used to secure non-metallic panels, such as carbon fiber panels. In this system, the steel, being at a lower potential than the carbon fiber, will corrode at a faster rate, while the carbon fiber panel will corrode at a slower rate. Again, when two materials with different anodic indices are in contact or close to each other, the potential for galvanic corrosion exists, with the material at the lower potential exhibiting accelerated corrosion.
[0007] Once an electrolyte is present, such as through the presence of non-distilled water, such as salt spray, corrosion can occur, which can weaken the structural integrity of any material used as an anode due to the relative electrode potentials of the materials, and / or cause poor aesthetic appearance. Galvanic corrosion is a problem in fields such as automotive and aerospace.
[0008] In the automotive industry, for example, there is a strong desire to reduce the weight of vehicles. This lightweighting is driven by efforts to improve fuel efficiency. Lightweight materials, such as aluminum, magnesium, and carbon fiber, are therefore used for body and drivetrain components. However, in many cases, the use of lightweight components does not allow for fasteners, such as bolts. Therefore, the bolts used are typically ferrous alloys, such as steel. The reluctance to use these lightweight materials in fasteners is due to their increased cost and the acceptance of steel fasteners, their strength and overall mechanical properties.
[0009] To prevent galvanic corrosion, similar materials or different materials with similar potentials (anodic index) can be used. However, this limits the type of combinations of materials that can be used for the desired application.
[0010] In another case, a barrier may be applied between different materials. For example, a bolt coated with a polymer material, such as nylon or a polymer sealing film, may be disposed between the bolt head and the panel. However, the nylon coating or sealing film may not prevent galvanic corrosion and may not meet the general mechanical requirements of the system. For example, the coating may be too thick and interfere with the engagement of the bolt with a female member (e.g., a nut), or may increase the coefficient of friction when the bolt is driven, or the elasticity of the coating or sealing film may result in a loss of tension when the system is subjected to temperature changes, such as heating and cooling. In addition, such a polymer coating or sealing film may not provide the barrier required to prevent electron transfer between different materials. Further, the elastic polymer material may not maintain structural integrity in situations where the system may be subjected to temperature fluctuations, vibrations, and other forces.
[0011] Therefore, there is a need for a method of preventing galvanic corrosion from occurring in a system having dissimilar materials in contact or proximity with each other in the presence of an electrolyte. Ideally, such a method would use materials that can withstand repeated heating and cooling of the system while protecting the materials from galvanic corrosion. Even more ideally, such a method would use materials that maintain the mechanical properties and requirements of the system. Even more ideally, such a method would be implementable in a manufacturing environment in a cost-effective manner.
[0012] There is also a need for a multi-part article system that exhibits resistance to galvanic corrosion under a variety of adverse environmental conditions while maintaining the required mechanical properties, conditions, characteristics and specifications of the system. Summary of the invention
[0013] According to an exemplary aspect, the present invention discloses an article of a first material, such as a metal article comprising at least one first surface, which is at least partially covered by a thermosetting coating. In some embodiments, the article is completely covered by a thermosetting coating. In different embodiments, the thermosetting coating is a fast-curing thermosetting coating. In certain embodiments, when the coating contacts the metal article and is exposed to an induction heater, the fast-curing thermosetting coating cures in about 1 minute or less. In other embodiments, the coating cures in about 30 seconds or less. In certain embodiments, when exposed to a temperature between about 350 and 475 degrees Fahrenheit, the coating will cure in any of the above time periods (or other). In certain embodiments, the thermosetting coating is a cross-linked epoxy coating, and may be a fusion-bonded epoxy coating.
[0014] In some embodiments, the thermosetting coating is made of a powder, such as an epoxy resin powder, which is subsequently cured to form a thermosetting coating. In various embodiments, the coating is made of a powder comprising an epoxy resin and one or more curing agents or hardeners. The curing agent or hardener may be composed of or include one or more amines, anhydrides, acids, phenols and / or alcohols. In certain embodiments, the thermosetting coating is made of a fused epoxy resin coating, such as Welding epoxy resin 413, Scotchkote 426FAST and / or AxaltaAlesta 74550. In some embodiments, the coating cures in about 30 seconds or less when subjected to a temperature of about 400 to 450 degrees Fahrenheit, in other embodiments about 420 to 430 degrees Fahrenheit, and in other embodiments about 425 degrees Fahrenheit after being applied to the article as a powder.
[0015] In various embodiments, the article further comprises a lubricant coating in contact with at least a portion of the article. In some embodiments, the lubricant coating covers or contacts at least a portion of the thermosetting coating, while in other embodiments, it covers the entire article and / or the entire surface of the thermosetting coating. In some embodiments, the lubricant coating consists of or comprises one or more waxes, for example, polyethylene wax, molybdenum disulfide, or one or more fluoropolymers.
[0016] In some embodiments, the thermosetting coating has a substantially uniform thickness. In various embodiments, the coating thickness (regardless of the geometry and / or shape of the article) deviates from the overall average coating thickness by only about 0.002 inches, and in other embodiments deviates from about 0.001 inches, and in other embodiments deviates from about 0.0005 inches. In certain embodiments, the thickness of the thermosetting coating is about 0.005 inches or less, and in other embodiments is about 0.0035 inches or less, or about 0.0025 inches or less, or about 0.0015 inches or less, or about 0.0010 inches or less, or about 0.0005 inches or less. In various embodiments, the thickness is between about 0.0005 and 0.005 inches, between about 0.0015 and 0.0035 inches, and about 0.0025 inches.
[0017] In certain embodiments, the article comprises an inorganic coating, including but not limited to a ceramic coating. In certain embodiments, the article is electroplated and / or plasma treated, for example, the article may comprise an Coatings. These embodiments may also comprise one or more thermoset coatings described herein and / or one or more lubricant coatings on top of an inorganic coating (e.g., ceramic coating) (i.e., article→ceramic coating→thermoset coating→lubricant coating→).
[0018] In certain embodiments, the thermoset coated article is heat resistant, e.g., it can be exposed to elevated temperatures for extended periods of time without adversely affecting the coating. For example, in certain embodiments, the coated article can withstand about 350 degrees Fahrenheit for about thirty minutes without adversely affecting the coating, such as softening, melting, flowing, dripping, charring, etc.
[0019] In some embodiments, the article is a fastener, such as a clip, bolt, clip or handle. The article may be composed of or include any metal or metal alloy. In certain embodiments, the article is iron or an iron alloy, such as steel. In other embodiments, such as when the article further includes a ceramic coating, the article is magnesium, aluminum, titanium or an alloy thereof.
[0020] In certain embodiments, the thermosetting coating comprises a first thermosetting coating, and a second thermosetting coating applied to the article on the first thermosetting coating, a portion thereof, or the entire surface of the article, including any or all portions already covered by the first thermosetting coating. In various embodiments, the first thermosetting coating is a fast-curing thermosetting coating and the second thermosetting coating is not a fast-curing thermosetting coating. For example, in some embodiments, when exposed to an induction heater while in contact with a metal article, the first thermosetting coating cures in about 1 minute or less, while the second thermosetting coating requires a longer curing time, such as more than ten minutes, or more than fifteen minutes, within the same temperature range used to cure the first thermosetting coating.
[0021] In some embodiments, the second thermosetting coating comprises one or more epoxy resins, polyesters or polyurethanes, while in other embodiments, the second thermosetting coating comprises an epoxy / polyester blend. In one embodiment, the second thermosetting coating comprises In various embodiments, the second thermosetting coating is only partially crosslinked, for example, when exposed to heat for a period of time shorter than that necessary to achieve full cure. These embodiments comprising a second thermosetting coating may also include a lubricant coating, for example, wherein the lubricant coating covers at least a portion of the top surface of the second thermosetting coating (i.e., article → first thermosetting coating → second thermosetting coating → lubricant coating).
[0022] According to another aspect, the present invention discloses an assembly comprising a first article and a second article configured to be fixed to or connected to the first article, wherein the two articles have different electrode potentials so that the articles can undergo galvanic corrosion in the presence of an electrolyte. The first article may be partially or completely coated with one or more thermosetting coatings, such as any coating described above or elsewhere in the present disclosure, and optionally partially or completely coated with a lubricant coating on the top surface of the thermosetting coating. In certain embodiments, the second article comprises, is connected to, or is configured to be connected to a third article. In different embodiments, the second article is also partially or completely coated with one or more thermosetting coatings, and optionally partially or completely coated with a lubricant coating on the top surface of the thermosetting coating. In certain embodiments, the second article may also include a non-thermosetting coating, such as a thermoplastic coating.
[0023] According to another aspect, the present invention discloses a method. In some embodiments, the method includes applying a powder coating to an article (e.g., by spraying the powder coating onto the article, optionally after the powder coating and / or the article has been subjected to the following process: generating an electric charge, such as a triboelectric charge, on the surface of the powder coating and / or the article). The method may also include transporting the powdered article to a heat source, such as an induction heater. In certain embodiments, the metal article is at room temperature or ambient temperature, and the powder is applied to the metal article, optionally after the powder coating and / or the article has been subjected to the following process: generating an electric charge, such as a triboelectric charge, on the surface of the powder coating and / or the article; and then, the article and powder coating are heated, such as by exposure to an induction heater, so that the powder cures into a cross-linked thermosetting coating. The method may further include: transporting the coated article to a lubrication station, in which one or more lubricants (e.g., a polyethylene wax emulsion) are applied to the article, such as by spraying.
[0024] The method may further include drying the lubricated article, such as by another application of induction heating. In some embodiments, another thermosetting coating is applied and at least partially cured on the article prior to lubrication. In certain embodiments, the method may include forming a ceramic coating on the article, followed by application of one or more thermosetting coatings (e.g., a fast-curing and then non-fast-curing thermosetting coating), and then optionally applying one or more lubricant coatings.
[0025] The present invention also discloses a method of inhibiting and / or preventing corrosion, such as galvanic corrosion of susceptible articles of a dual article system, wherein the first and second articles of the dual article system have surfaces facing each other, and wherein the two articles are composed of materials having different anodic indices, the method comprising: applying a coating to a surface of the first article, curing the coating on the surface of the first article, and contacting and fixing the surface of the first article with the surface of the second article so that the two articles exhibit substantially no galvanic corrosion after exposure to a corrosive environment in accordance with the standard General Motors Global Engineering Standard Test Procedure GMW17026, "Accelerated Corrosion Laboratory Test for Galvanic Corrosion Mechanisms". In one embodiment of the method, when the cured coating is present on at least the head of a steel bolt mounted to a magnesium coupon, the magnesium coupon exhibits less than about 20%, 10%, 5%, 3% or 1% pitting after exposure to a corrosive environment in accordance with the standard GMW17026, simulated exposure test for 15 years.
[0026] In an embodiment of a method for inhibiting and / or preventing corrosion (e.g., galvanic corrosion), the coating is a thermosetting material. The thermosetting material may be an epoxy material that crosslinks during curing to form a crosslinked epoxy coating. One such epoxy material is a welded epoxy material. The epoxy material may also include a curing agent or hardener, such as one or more polyamines, anhydrides, acids, phenols, alcohols, and thiols. The epoxy material may also include one or more fillers and pigments. In one method, the epoxy material is cured in about 30 seconds or less when subjected to a temperature of about 400 to 450 degrees Fahrenheit to form a crosslinked epoxy coating.
[0027] The method may comprise applying the coating as a powder. The powder may be sprayed onto the article, for example after an electrical charge has been applied to the powder and / or the article.
[0028] In one method, the coating comprises a first coating and a second coating, so that the first coating is completely cured to form a first cured layer, and the second coating is applied to the first cured layer. The second coating may be a thermosetting material. The first coating may be a fast curing material, and the second coating may cure at a slower rate than the first coating.
[0029] In one method, the curing is thermal curing. The thermal curing may be induction heat curing and may include subjecting the article to a magnetic field after the thermosetting material has been applied to at least a portion of the surface of the article.
[0030] In one embodiment of the method, the second coating is a lubricant. The lubricant may be one or more of polyethylene wax, paraffin wax, carnauba wax and a solid lubricant. The solid lubricant may be one or more of molybdenum disulfide and a fluorine-containing polymer.
[0031] In one embodiment of the method, the cured coating has a substantially uniform thickness of about 0.005 inches or less, and in other embodiments about 0.0035 inches or less, or about 0.0025 inches or less, or about 0.0015 inches or less, or about 0.0010 inches or less, or about 0.0005 inches or less. In various embodiments, the thickness is between about 0.0005 and 0.005 inches, between about 0.0015 and 0.0035 inches, and about 0.0025 inches. The thickness may be about 0.0015 inches.
[0032] In the method, the first and second articles can be made of dissimilar metals. For example, the first article can be made of iron or an iron alloy, and the second article can be made of magnesium or a magnesium alloy, aluminum or an aluminum alloy, or titanium or a titanium alloy. One of the first and second articles can be made of a non-metal (e.g., a carbon-based material such as graphite, such as a carbon fiber material). The first article and the second article can be made of materials having different anodic indices, for example, the anodic indices differ by at least 0.1, 0.2, 0.3, 0.4, 0.5 or more.
[0033] The first article may have an anodic index less than that of the second article. The first article may comprise iron or an iron alloy, and the second article may comprise magnesium or a magnesium alloy. Alternatively, the second article may comprise aluminum or an aluminum alloy.
[0034] The first article may be a male fastener, such as a bolt or a screw. In this method, the bolt may exhibit no more than about 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10% or less loss in tension when heated to a temperature of at least about 125°C for 800 hours, and no more than about 25%, 20%, 15%, 10%, 5% or less loss in tension when thermally cycled at a temperature between -40°C and 80°C (about -40 to 176°F) for 13 cycles and held at each temperature for 3 hours.
[0035] The present invention also discloses a dual product system having a first and a second product, wherein the first and the second products have surfaces facing each other, wherein the two products have different anodic indices, and wherein the surface of the first product comprises a coating formed by curing a coating on the surface of the first product, and the surface of the first product is in contact with and fixed to the surface of the second product. The two products are subjected to a 15-year simulated exposure test according to standard GMW17026, and after exposure to a corrosive environment, substantially no galvanic corrosion is exhibited. In one embodiment of the system, when the cured coating is present on at least the head of a steel bolt mounted on a magnesium test piece, the magnesium test piece exhibits less than about 20%, 10%, 5%, 3% or 1% pitting compared to an uncoated steel bolt mounted on the magnesium test piece after a 15-year simulated test according to standard GMW17026.
[0036] In one embodiment, the coating is a thermosetting material. The thermosetting material can be a cross-linked epoxy coating, such as a welded epoxy material. In one embodiment, the epoxy material contains a curing agent or a hardener. The curing agent or the hardener can contain one or more of a polyamine, anhydride, acid, phenol, alcohol and thiol. In one embodiment, the epoxy material contains one or more fillers and pigments. The epoxy material can cure in about 30 seconds or less when subjected to a temperature of about 400 to 450 degrees Fahrenheit to form a cross-linked epoxy coating.
[0037] In one embodiment, the coating comprises a first coating and a second coating, such that the first coating is fully cured to form a first cured layer, and the second coating is applied to at least a portion of an outer surface of the first cured layer to form the coating.
[0038] The second coating may be a thermosetting material, and the first coating may be a fast curing material, so that the second coating cures at a slower rate than the first coating. In one embodiment, the second coating is a lubricant. The lubricant may be one or more of polyethylene wax, paraffin wax, carnauba wax and a solid lubricant. The solid lubricant may be one or more of molybdenum disulfide and a fluorine-containing polymer.
[0039] In one embodiment, the cured coating has a substantially uniform thickness of about 0.0001 to 0.005 inches. The thickness of the thermosetting coating may be about 0.005 inches or less, about 0.0035 inches or less, about 0.0025 inches or less, about 0.0015 inches or less, about 0.0010 inches or less, or about 0.0005 inches or less. In various embodiments, the thickness is between about 0.0005 and 0.005 inches, between about 0.0015 and 0.0035 inches, and about 0.0025 inches.
[0040] In one system, the first article and the second article are dissimilar metals. One of the first and second articles may be a non-metal. The first article may be a steel bolt and the second article may be formed of a metal having a smaller anodic index. The second article may be formed of magnesium, and the cured coating may be present on at least the head of the steel bolt such that when mounted to a magnesium coupon, the magnesium coupon exhibits less than about 20%, 10%, 5%, 3% or 1% pitting compared to the uncoated steel bolt on the magnesium coupon when the coupon with the uncoated steel bolt exhibits pinhole perforation (or through-wall perforation) after 15 years of simulated exposure testing according to test procedure GMW17026.
[0041] In one embodiment, the first article has an anodic index greater than the second article. The first article may comprise iron or an iron alloy. The second article may comprise magnesium or a magnesium alloy or aluminum or an aluminum alloy.
[0042] In one system, the first article is a male fastener. The male fastener can be a bolt or a screw. In this system, the screw can exhibit a tension loss of no more than about 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10% or less when heated to a temperature of at least about 125°C for about 800 hours, and a tension loss of no more than about 25%, 20%, 15%, 10%, 5% or less when the screw is thermally cycled for 13 cycles at a temperature between about -40°C and 80°C (about -40 to 176°F) and held at each temperature for 3 hours.
[0043] In one embodiment, the first article is a steel bolt, and the coating is present on at least one head of the steel bolt and an underside of the head of the steel bolt. Optionally, if the bolt includes a flange, the coating may be present on at least a portion of the flange. Optionally, the coating may be present on at least a portion of the threads on the bolt shank of the bolt.
[0044] Other objects, features and advantages of the present invention will become apparent from the following description when read in conjunction with the accompanying drawings in which like numerals represent like parts, elements, components, steps and processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 is a schematic diagram of a fastener having a thermosetting coating thereon according to one embodiment, wherein for ease of illustration, the fastener is shown having a face plate and an underlying structure in a partially exploded view;
[0046] Figure 2 Two exemplary articles of manufacture according to the present invention are shown, one without any coating and the other having a thermosetting coating applied to a portion thereof;
[0047] Figure 3 shows a cross-sectional view of an exemplary article after application of a thermosetting coating according to the present invention;
[0048] Figure 4 A schematic diagram showing an exemplary article coated with a different thermosetting coating having a thickness different from that of the thermosetting coating described in the present invention;
[0049] Figure 5 An exemplary product structure is shown for implementing certain embodiments of the methods described in the present invention;
[0050] Fig. 6A, 6B, 6C show schematic diagrams of exemplary components of the assembly of the present invention, or assembled components of the exemplary assembly, wherein, Fig. 6A and 6B Provides views of non-thermoset coated articles configured to be secured to a Figure 6C The coated article shown;
[0051] Figure 7 is a photograph of a test assembly in which two sample steel bolts are mounted on a carbon fiber sample panel, the bolt at the bottom of the figure having a thermoset coating according to an embodiment of the present invention and the bolt at the top of the figure not having such a coating;
[0052] Figure 8 is a table showing the relative anodic index of various common materials, with the lowest potential material shown at the top of the table and higher potential materials shown at the bottom of the table;
[0053] Figures 9A-9G All are photos, visually showing the results of simulated corrosion tests of undamaged uncoated bolts (right) and undamaged thermosetting coated bolts (left) in magnesium test pieces in a corrosive environment according to standard GMW17026 and at simulated exposures of 1 year, 2 years, 3 years, 4 years, 5 years and 8-9 years; wherein, Fig. 9A The bolt and test piece are shown before testing. Fig. 9B The bolts and test pieces are shown after simulating a one-year exposure. Fig. 9C The bolts and test pieces are shown after simulating two years of exposure. Fig.9D The bolts and test pieces are shown after simulating three years of exposure. Fig.9E The bolts and test pieces are shown after simulating four years of exposure. Fig.9F shows the bolts and coupons simulated for five years of exposure, and Figure 9G Bolts and coupons simulated for eight to nine years of exposure are shown;
[0054] Fig.10 is a photograph of a magnesium test piece after 15 years of simulated exposure testing in a corrosive environment according to standard GMW17026, with an undamaged uncoated bolt (right) and an undamaged thermoset coated bolt (left) mounted to the test piece;
[0055] Figures 11A-11L All are photographs, visually showing the results of simulated corrosion tests of carbon fiber test pieces with undamaged uncoated bolts (left) and undamaged thermosetting coated bolts (right) mounted to the test pieces in a corrosive environment according to standard GMW17026 and at 1, 2, 3, 4, 5, 10, 11, 12, 13, 14 and 15 years of exposure; wherein, Fig.11A The bolt and test piece are shown before testing. Fig. 11B The bolts and test pieces are shown after simulating one year of exposure. Fig. 11C The bolts and test pieces are shown after simulating two years of exposure. Fig.11D The bolts and test pieces are shown after simulating three years of exposure. Fig.11E The bolts and test pieces are shown after simulating four years of exposure. Fig.11F shows the bolts and coupons simulated for five years of exposure, and Fig.11G The bolt and test piece are shown after simulating ten years of exposure. Fig.11H The bolt and test piece are shown after 11 years of simulated exposure. Fig.11I The bolt and test piece are shown after simulating twelve years of exposure. Fig.11J The bolt and test piece are shown after 13 years of simulated exposure. Figure 11K shows the bolts and coupons simulated for fourteen years of exposure, and Fig.11L shows the bolt and coupon simulated for fifteen years of exposure; and
[0056] Figures 12A-12L All are photographs, visually showing the results of simulated corrosion tests of carbon fiber test pieces with damaged uncoated bolts (right) and damaged thermosetting coated bolts (left) mounted to the test pieces in a corrosive environment according to standard GMW17026 and at 1, 2, 3, 4, 5, 10, 11, 12, 13, 14 and 15 years of exposure; wherein, Fig. 12A The bolt and test piece are shown before testing. Fig. 12B The bolts and test pieces are shown after simulating one year of exposure. Fig. 12C The bolts and test pieces are shown after simulating two years of exposure. Fig.12D The bolts and test pieces are shown after simulating three years of exposure. Fig.12E The bolts and test pieces are shown after simulating four years of exposure. Fig.12F shows the bolts and coupons simulated for five years of exposure, and Figure 12G The bolt and test piece are shown after simulating ten years of exposure. Fig.12H The bolt and test piece are shown after 11 years of simulated exposure. Fig.12I The bolt and test piece are shown after simulating twelve years of exposure. Fig.12J The bolt and test piece are shown after 13 years of simulated exposure. Figure 12K shows the bolts and coupons simulated for fourteen years of exposure, and Figure 12L Shown are bolts and coupons simulated for fifteen years of exposure. DETAILED DESCRIPTION
[0057] The present invention is further described below in conjunction with specific implementation modes, but the present invention is not limited to the following implementation modes.
[0058] Embodiments described herein provide apparatus and methods, and in particular provide a system, wherein at least two articles of different materials, such as Figure 8 Any material shown in the table in , and at least one of the articles is at least partially coated with a material capable of preventing galvanic corrosion. For example, such a system may be an assembly having two dissimilar metals in contact with each other in the presence of an electrolyte, or a metal of the assembly is in contact with a non-metal, such as a carbon fiber material, etc. The present invention also discloses a method for preventing galvanic corrosion in such a system. In a non-limiting embodiment, a steel component such as a steel bolt is partially or fully coated with a material capable of preventing galvanic corrosion, wherein the bolt is used to fix a chrome article, a magnesium article, an aluminum article, a stainless steel article or a carbon fiber article, such as a pot, panel or applique to a structure, such as a housing, or an underlying structure, without negatively affecting the mechanical properties, requirements, conditions and specifications of the system. It is understood that, for example, the methods and systems described in the present invention protect underlying components, such as a magnesium oil pot, when using steel bolts to fix to a housing, and protect steel bolts when used to fix a carbon fiber panel to an underlying structure, noting that, as Figure 8 As shown, steel is located at approximately the midpoint of the anodic index spectrum, while magnesium and carbon fiber are located at opposite ends of the anodic index spectrum.
[0059] These and other aspects, features and advantages of the present invention, or features and advantages of certain embodiments of the present invention, will be further understood by those skilled in the art based on the following description of exemplary embodiments. Among other advantages, the coated articles of the present invention can be produced very quickly by high-volume manufacturing processes, have high strength / durability / scratch resistance, and can withstand high temperatures for a long time. In addition, the coated articles have been found to exhibit good chemical resistance in automotive applications, such as motor oil, fuel (diesel, gasoline, bio-based and composite fuels, such as alcohol-based fuels), power steering fluid, windshield washer fluid, etc.
[0060] According to one exemplary aspect, a metal article is disclosed that includes at least a first surface at least partially covered by a thermosetting coating.
[0061] Figure 1 One such embodiment is shown. Figure 1 Here, the coated bolts 1 are used to secure a panel P (such as a transmission oil pan) to a transmission case C. Figure 11 , the head 2 of the bolt 1, the flange 3 of the bolt 1, and a portion 4 of the shank 5 are coated with a thermosetting coating 6. The bolt 1 may be made of steel, the face plate or pot P may be made of magnesium, and the underlying structure or housing C may be made of aluminum. It will be appreciated that the magnesium pot P is significantly more anodic than the steel of the bolt 1, and is therefore susceptible to galvanic corrosion. In the illustrated example, the coating 6 is present on the head 2 and flange 3, and along the portion 4 of the threads on the shank 5 of the bolt 1, and thus provides a barrier between the bolt 1 and the pot P to prevent and / or inhibit galvanic corrosion. It will be appreciated that the extent of the coating may be greater or lesser, depending on the application.
[0062] Figure 2 Other illustrative examples of coated and uncoated articles are provided. Figure 2 In the embodiment, an uncoated article 10 (in this embodiment, a different form of a bolt) has a threaded portion 14 and a fastener assembly 12 configured to receive a second article, the fastener assembly comprising a first wear surface 16, a second wear surface 18 (in this embodiment, the head of the bolt), and a connecting portion 17. In this embodiment, the surface of the fastener assembly is configured to contact an article made of dissimilar metals. Figure 1 Also shown is a coated article 20, wherein a portion of the article has a thermosetting coating. While in some embodiments, the article is completely covered with the thermosetting coating, in other embodiments, only a portion or portions of the article are coated. Figure 2 In the illustrated embodiment, the entire fastener assembly 22 of the coated article 20 is covered by the thermoset coating, including the threaded portion 24, providing coated wear surfaces 26 and 28 and the coated connection 27. However, it should be noted that in some embodiments, the threaded portion 24 may not be coated.
[0063] As a representative embodiment, the coated article can be connected to or incorporated into a larger component through or by an uncoated portion (such as the threaded portion 24 described herein), and then another metal or non-metal component having a different galvanic potential or electrode potential or anodic index is connected or fixed to the fastening component. Based on the components to be connected together, the fastening component can have any desired suitable size, geometry or configuration. In many embodiments, the article includes one or more grooves, recesses, channels, cavities or other structural features configured to interact with or be fixed to appropriate structural features on a second article, wherein the interior of the grooves, etc. is coated with one or more layers of coating. In other embodiments, the coated article does not have any type of fastening component, but is configured to simply contact dissimilar metal or non-metal components having different galvanic potentials or electrode potentials or anodic indices, so that galvanic corrosion can otherwise occur without a thermosetting coating.
[0064] exist Figure 2 In the illustrative embodiment shown, the primary wear protection is desired in the slot defined by and between the portions 26 and 28, where, for example, a chrome plated applique component ultimately slides into the slot between the two plates. In some embodiments, such as Figure 2 In the illustrated coated article 20, any and all surfaces in the component that are wear surfaces are coated with a thermosetting coating (or coatings as described in more detail below), while in other embodiments, only specific wear surfaces are coated. Using the coated article 20 as an example, other embodiments apply the coating only to the inner surface of the fastener component 22 that is defined or located within the slot and ultimately contacts dissimilar metal or non-metal components having different galvanic potentials or electrode potentials or anodic indices, rather than the outward-facing surfaces of the same component.
[0065] The articles, components, systems and methods disclosed herein include or use thermosetting materials as coatings. As understood in the art, thermosetting materials include a prepolymer that is irreversibly cured after exposure to heat (generally above 392°F), chemical reaction and / or suitable irradiation. Therefore, the thermosetting materials included or used in the articles, components, systems and methods disclosed herein can be cured by any suitable means, including: heat, chemical reaction and / or suitable irradiation. Suitable heating methods for curing thermosetting materials may include, but are not limited to: subjecting the thermosetting material to heat generated by induction. Examples of thermosetting materials suitable for the disclosed articles, components, systems and methods include, but are not limited to: epoxy resin materials, such as epoxy resins or polyepoxides, polyesters or polyester resin materials, polyurethane materials, vulcanized rubber materials, phenolic resin materials, such as bakelite, melamine materials, diallyl phthalate (DAP) materials, polyimide materials, and cyanate ester or polycyanurate materials. Alternatively, the thermoset material may include a prepolymer and a hardener (eg, a co-reactant including a multifunctional amine, acid (and anhydride), phenol, alcohol and / or thiol).
[0066] In various embodiments, the thermosetting coating is a fast-curing thermosetting coating. In certain embodiments, the fast-curing thermosetting coating cures in about 1 minute or less when the coating is in contact with the metal article and exposed to an induction heater; in other embodiments, the coating cures in about 30 seconds or less. In certain embodiments, the coating cures in any of the above time periods (or others) when exposed to a temperature between about 350 and 475 degrees Fahrenheit. In certain embodiments, the coating cures in about 30 seconds or less when the coating is subjected to a temperature of about 400 to 450 degrees Fahrenheit after being applied to the article as a powder, in other embodiments, when subjected to a temperature of about 350 to 490 degrees Fahrenheit, in other embodiments, when subjected to a temperature of about 420 to 430 degrees Fahrenheit, and in other embodiments, when subjected to about 425 degrees Fahrenheit.
[0067] In various embodiments, the thermosetting coating comprises an epoxy resin material, such as an epoxy resin material or a polyepoxide material. The epoxy resin material of the thermosetting coating can react (crosslink) with itself by catalytic homopolymerization, or react (crosslink) with various co-reactants, including: multifunctional amines, acids (and anhydrides), phenols, alcohols and thiols. These co-reactants can be hardeners or curing agents, and the crosslinking reaction can be referred to as curing. Epoxy materials suitable for thermosetting coatings may include, but are not limited to, bisphenol A epoxy materials (e.g., formed by combining epichlorohydrin and bisphenol A to form bisphenol A diglycidyl ether), bisphenol F epoxy materials, epoxy phenol novolac materials and epoxy cresol novolac materials (e.g., formed by reacting phenol with formaldehyde and subsequently glycidylating with epichlorohydrin), aliphatic epoxy materials (e.g., formed by glycidylating an aliphatic alcohol or polyol), and glycidyl epoxy materials (e.g., formed when an aromatic amine is reacted with epichlorohydrin).
[0068] In various embodiments, the thermosetting coating is a cross-linked epoxy coating. The coating may be a fused epoxy coating. In some embodiments, the thermosetting coating is made of a powder, such as an epoxy powder, which is subsequently cured / cross-linked to form a thermosetting coating; while in other embodiments, the thermosetting coating is made of a liquid precursor. In various embodiments, the coating is made of a powder comprising an epoxy resin and one or more curing agents or hardeners. The curing agent or hardener may be composed of or contain one or more amines (e.g., aromatic amines, aliphatic diamines), anhydrides, acids, phenols, alcohols and / or thiols. In some embodiments, the powder further comprises one or more fillers and / or one or more pigments, or other additional ingredients. In certain embodiments, by using a fused epoxy coating, the thermosetting coating is made of Welding epoxy resin 413, Made of Scotchkote 426FAST and / or Axalta Alesta 74550.
[0069] The crosslinked thermoset coatings provide high strength and durability for use in a variety of applications where the coating is exposed to abrasive forces, for example, providing greater durability than nylon coatings and / or thermoplastic coatings known in the art. The use of certain epoxy resins identified above can also advantageously provide strong adhesion to the article substrate (compared to nylon thermoplastic coatings), good impact resistance and / or improved scratch / abrasion resistance. For example, having An exemplary article of fusion bonded epoxy 413 to form the disclosed thermoset coating had scratches only on the top surface in the area in contact with the article after repeated insertion of the part which could result in removal of the nylon thermoset coating, based on microscopic analysis.
[0070] In various embodiments, the article further comprises a lubricant coating in contact with at least a portion of the article. In some embodiments, the lubricant coating covers or contacts at least a portion of the thermosetting coating, while in other embodiments, it covers the entire article and / or the entire surface of the thermosetting coating. In some embodiments, the lubricant is applied to surfaces such as bolt threads and bearing surfaces that are exposed to forces when the article is used, such as fasteners. As a representative embodiment, Figure 2The coated article 20 shown in may have a lubricant coating only on the surfaces of the fastening components (e.g., coated wear surfaces 26 and 28 and coated connection 27) or may have a lubricant coating only on the surface subjected to the greatest force, which in this embodiment is connection 27. The lubricant may be a solid or liquid lubricant. In some embodiments, the lubricant coating is composed of or includes one or more waxes, for example, one or more polyethylene waxes, paraffin wax, carnauba wax, solid lubricants such as molybdenum disulfide or one or more fluoropolymers (e.g., polytetrafluoroethylene). Figure 1 In the bolt shown, lubricant may be present on the thread 5 to achieve the desired friction coefficient and / or on the underside of the flange 3 .
[0071] In some embodiments, the thermosetting coating has a substantially uniform thickness. In various embodiments, the coating thickness (regardless of the geometry and / or shape of the article) deviates from the overall average coating thickness by only about 0.002 inches, and in other embodiments deviates from about 0.001 inches, and in other embodiments deviates from about 0.0005 inches. In certain embodiments, the thickness of the thermosetting coating is about 0.005 inches or less, and in other embodiments is about 0.0035 inches or less, or about 0.0025 inches or less, or about 0.0015 inches or less, or about 0.0010 inches or less, or about 0.0005 inches or less. In various embodiments, the thickness is between about 0.0005 and 0.005 inches, between about 0.0015 and 0.0035 inches, and about 0.0025 inches.
[0072] In certain embodiments, the article comprises an inorganic coating, such as a ceramic coating, and / or is electroplated and / or plasma treated. For example, the article may comprise a In some embodiments, the aluminum article is coated with the The coating, wherein it can be used with magnesium articles, as one skilled in the art will appreciate, is pre-treated for galvanic corrosion given its location on the anode index. By coating aluminum fasteners that will serve as cathodes, even when using materials such as magnesium, these embodiments provide a barrier to galvanic corrosion. This advantageously allows magnesium parts to be coupled without the use of expensive parts currently known in the prior art. Further, by coating the aluminum cathode, these embodiments can avoid potential problems caused by coating magnesium parts, since any microscopic pores in the magnesium coating can lead to galvanic corrosion in concentrated areas of magnesium (such as degradation due to its role as an anode in a galvanic cell), which can detrimentally weaken the structural integrity of the part, especially if the concentrated corrosion is located in a critical location of the part. In yet other embodiments, for example, as described herein, the magnesium surface can be coated with a ceramic coating, and in some embodiments, aluminum and magnesium flakes can be coated and used together to further inhibit the possibility of corrosion. Any of these embodiments may also include one or more thermosetting coatings described herein and / or one or more lubricant coatings on top of an inorganic coating (e.g., a ceramic coating). This may provide additional benefits when the inorganic coating is somewhat porous or has surface irregularities (but still provides a coating sufficient to prevent galvanic corrosion). The ceramic coating has pores that can be filled with the thermoset coating to help improve adhesion and provide a more comprehensive barrier to electrical current.
[0073] In certain embodiments, the thermoset coated article has heat resistance such that it can be exposed to elevated temperatures for extended periods of time without adversely affecting the coating, such as softening, melting, flowing, dripping, charring, etc. For example, in certain embodiments, the coated article can withstand temperatures of about 350 degrees Fahrenheit for about thirty minutes without adversely affecting the coating. The epoxy thermosetting resins identified above, such as Welding epoxy resin 413, Scotchkote 426FAST and / or Axalta Alesta 74550, provide coatings with these improved levels of heat resistance, meaning that the coatings will not melt and / or flow out when exposed to these types of thermal conditions. This is beneficial, for example, in embodiments where the coated article is exposed to additional manufacturing processes. Steel clips designed to secure aluminum fenders to automobile bodies are an example of such embodiments, as these parts may be exposed to high temperatures (including the thirty minute, 350 degree Fahrenheit condition described above) during automobile production.
[0074] Figure 3 and Figure 4 Provided are exemplary materials coated Welding epoxy resin 413 ( Figure 3 )and Scotchkote426FAST( Figure 4 ) is an exemplary view of an article. Figure 3 In the embodiment shown, a steel fastener 30A is coated with The epoxy resin 413 is fused and heated to a curing temperature by induction heating, providing a substantially uniform thermosetting coating 32A (exterior material). Figure 4 In the embodiment shown, a steel fastener 30B is coated with Scotchkote 426FAST and is heated by induction (with Figure 3 ) is heated to a curing temperature to provide a thermosetting coating 32B (with Figure 3 The outer material does not have such a uniform thickness compared to the embodiment shown in ).
[0075] In some embodiments, the article is a fastener, such as a bolt, a clip, or a handle. The article may be composed of or include any metal or metal alloy. In certain embodiments, the article is steel. In other embodiments, such as but not limited to, the article further includes a ceramic coating, and the article is magnesium, aluminum, titanium, or an alloy thereof. In some embodiments, the article is composed of or includes steel, stainless steel, titanium, nickel, copper, bronze, brass, tin, lead, iron, aluminum, zinc, magnesium, or an alloy thereof. For example, such a clip may be a steel clip that may be used to mount an aluminum fender on a vehicle. Such a clip may be completely coated with an exemplary Welding epoxy resin 413, Scotchkote 426FAST and / or AxaltaAlesta 74550, but other cross-linked thermosetting resins will be used as described herein, or for example they may be partially coated on a single surface or a subset of all surfaces.
[0076] In certain embodiments, the thermoset coating comprises a first thermoset coating, and a second thermoset coating applied to the article over the first thermoset coating, a portion thereof, or the entire surface of the article, including any portion already covered by the first thermoset coating. In various embodiments, the first thermoset coating is a fast-curing thermoset coating and the second thermoset coating is not a fast-curing thermoset coating. For example, in some embodiments, when exposed to an induction heater while in contact with a metal article, the first thermoset coating cures in about 1 minute or less, while the second thermoset coating requires a longer curing time, such as more than ten minutes, or more than fifteen minutes, within the same temperature range used to cure the first thermoset coating. In some embodiments, the second thermoset coating comprises one or more epoxy resins, polyesters, or polyurethanes, while in other embodiments, the second thermoset coating comprises an epoxy / polyester mixture. In one embodiment, the second thermoset coating is composed of a powder. Made of TGIC polyester (such as PRA60001).
[0077] As an example, the polyester material has poor impact resistance when applied to steel fasteners when it is the only coating - but when applied over another thermoset coating, in this exemplary embodiment, The results were surprisingly different in the fusion epoxy 413. The bonded coatings exhibited high impact resistance even when the polyester material was not fully crosslinked (e.g., because it was only exposed to induction heating for the same time used to cure a fast-curing thermoset resin), and surprisingly high adhesion despite incomplete cure to an underlying thermoset coating, such as an epoxy.
[0078] Thus, in various embodiments, the second thermosetting coating is only partially crosslinked, for example, when it is exposed to heat for a period of time shorter than the time necessary to achieve full cure. This advantageously still allows slower curing materials to be incorporated into high-speed, high-volume manufacturing processes, if desired, but still provides improved and enhanced coated articles. In certain embodiments, a fast-curing thermosetting coating is applied to a substrate, rapidly cured by heat (such as induction heating), and then a second coating is applied and partially cured (or in some embodiments, fully cured, albeit requiring a longer cure time). These embodiments comprising a second thermosetting coating may also include a lubricant coating.
[0079] The description of these articles is only an example. In certain embodiments, the articles include additional combinations or substitutes of some or all of the above-mentioned components. In addition, in view of the beneficial effects of the present invention, additional and alternative suitable variants, forms and components for the articles will be recognized by those skilled in the art.
[0080] Other aspects of the invention relate to an assembly that may include a first article and a second article configured to be fixed to, connected to, or adjacent to the first article, wherein the two articles have different electrode potentials (anodic indexes) so that the articles can undergo galvanic corrosion in the presence of an electrolyte. The first article may be partially or fully coated with one or more thermosetting coatings, such as any coating described above or elsewhere in this disclosure, and optionally a lubricant coating.
[0081] In certain embodiments, the second article comprises, is connected to, or is configured to be connected to a third article (e.g., an automobile or a part thereof). An assembly having an article with one or more coatings as described herein may comprise automotive or aerospace materials, such as fasteners, clips, or other connecting materials. Still other possible articles for use in the assembly may be fasteners for decorative automotive appliques or other automotive materials, such as, but not limited to, buckles, clips, or fastening articles used with fenders or oil pans, including a magnesium oil pan. For example, FIG. 6 shows an illustration of an applique assembly, wherein, Fig. 6A and 6B A view of an uncoated article is provided, e.g. Figure 6C A chrome plated appliqué 38 is shown configured to be secured to a coated fastener wherein the fastener is Figure 2 The coated articles 20 shown are the same or substantially similar.
[0082] Figure 7 is a photograph showing an example in which two sample steel bolts are mounted on a carbon fiber sample panel after a 15-year simulation test in a corrosive environment according to standard GMW17026. The upper bolt in the photograph is not coated with a thermosetting coating, while the lower bolt in the photograph is coated with a thermosetting coating. It is obvious that the uncoated bolt has significant corrosion, while the bolt coated with the thermosetting material shows almost no corrosion. It can therefore be understood that the sample bolts in the photograph exhibit the corrosion resistance provided by the thermosetting coating of the present invention.
[0083] The description of these components is exemplary only. In some embodiments, the components include additional combinations or alternatives of some or all of the above components. In addition, in view of the beneficial effects of the present invention, additional and alternative suitable variations, forms and components for the components will be recognized by those skilled in the art. In addition, any feature disclosed in the exemplary embodiments of the above-mentioned articles can be a feature of an embodiment of a component or its components, and vice versa.
[0084] Other aspects of the present invention relate to a method. In some embodiments, the method includes applying a powder coating to an article (e.g., by spraying the powder coating onto the article). The powder precursor material may be suspended in an air stream and sprayed onto the article using a suitable spray gun, which may ionize the powder so that the powder is properly applied to the metal article before curing. In some embodiments, a triboelectric method is used to ensure that recessed or difficult to properly reach areas receive the powder coating, such as using heavy electrostatic forces to cause a cage effect that prevents these areas from being coated with the powder. In certain embodiments, the powder passes through a thermoplastic material in a spray gun to obtain the desired charge. Other application methods are also feasible, but, for example, the article may be immersed in a powder precursor bed. For embodiments where it is difficult to reach surfaces or internal surfaces that need to be coated, additional spray gun accessories or extensions may be used. In other embodiments, one or more barriers may be arranged between the spray gun and the article so that only a portion or portions of the article are covered with powder (and therefore, ultimately coated with a thermosetting coating). In certain embodiments, the article is cleaned and / or scraped and / or primed to promote adhesion of the coating precursor material prior to curing.
[0085] The method may also include heating the powdered article. In some embodiments, the method may include transporting the powdered article to a heat source, such as an induction heater that applies a magnetic field. In certain embodiments, the metal article is at room temperature or ambient temperature, the powder is applied to the metal article, and then the article and powder are heated, such as by exposure to an induction heater, to cure the powder into a cross-linked thermosetting coating. In other embodiments, the article may be heated at the same location where the powder is applied, or the article may be heated prior to applying the powder, so that any residual heat in the metal provides for curing or at least partially curing the powder. Embodiments of the method in which the powder is applied to a room temperature article are preferred, however, provide a relatively simplified manufacturing process.
[0086] By using any conveying system known in the art, such as a conveyor belt, one or more gripping wheels, a rotating table, or Figure 5 Schematically shown is a magnetic table 50 to which the article may be transported (for this step or others). In some embodiments, the conveyor carries the article into and past a heat source, such as an induction heater 52. In other embodiments, one or more components are moved or transported adjacent to the article, which remain stationary, such as a powder spray gun 46, where the powder 48 is applied to the article. An air stream (not shown) may be used to blow excess material from the article.
[0087] Other possible heating methods include: using infrared heat and / or other thermal radiation, curing ovens, heat tunnels, heat guns, or bringing the heat source into direct contact with the article to transfer heat by conduction, etc. Depending on the characteristics of the coating (e.g., the resin and any curing agent composition) and the specific method, the temperature used to cure the powder can be any of the temperatures previously described (i.e., between about 350 and 490 degrees Fahrenheit, or about 425 degrees Fahrenheit, or others).
[0088] For example, in some embodiments, heat is applied for 5 seconds or less, in other embodiments for 10 seconds or less, and in other embodiments for 15 seconds or less, 30 seconds or less, 60 seconds or less. In other embodiments, methods may be required that use longer curing materials or lower temperatures, longer times on the order of minutes (e.g., 2 minutes or less, 5 minutes or less, 10 minutes or less, 15 minutes or less, or 30 minutes or less). However, in view of the advantages provided by manufacturing speed, embodiments that allow at least the base thermosetting layer to be fully cured or nearly fully cured in a shorter time frame are preferred.
[0089] The method may also include transporting the coated article to a lubrication station, where one or more lubricants (e.g., polyethylene wax emulsion) are applied to the article, such as by spraying or dipping. The method may also include drying the lubricated article, such as by another application of induction heating or using another heat source (or even the same heat source used to cure the resin into a cross-linked material). In various embodiments, additional heat is not provided, and the article is air dried or does not need to be dried, based on the choice of lubricant (e.g., when a dry lubricant such as molybdenum disulfide is used). In some embodiments, shorter heat is applied to the extent necessary to dry the lubricated article, such as applying induction heat for one to two seconds. This further contributes to the manufacturing efficiency of the method.
[0090] In some embodiments, a second thermosetting coating is applied and at least partially cured on the article prior to lubrication. In certain embodiments, the method may include forming a ceramic coating on the article, then applying one or more thermosetting coatings (e.g., a fast-curing then a non-fast-curing thermosetting coating), and then optionally applying one or more lubricant coatings.
[0091] As mentioned above, Figure 5An exemplary system for implementing an embodiment of the method is shown. In this embodiment, the system includes a magnetic table that holds and transports a plurality of articles, which in these embodiments are at room temperature. In step A of this exemplary method, a spray gun applies a powdered precursor material (e.g., a powdered epoxy resin) to the articles, which are then conveyed to a location between induction heaters. In step B, the heaters apply heat to cure the powder and result in a cross-linked thermosetting coating on the articles. Optionally, the magnetic table then conveys the coated articles to a lubricant applicator, such as a spray gun, which applies lubricant in step C. The magnetic table then conveys the finished product to a finishing location for removal from the table in exemplary step D. It will be appreciated that, for example, the method allows for selective application of the coating to the head of a bolt, the head and flange (if present) of a bolt, the underside of the head, and, if desired, the threads or a portion of the threads of a bolt.
[0092] Various samples of the assembly were tested to determine the effectiveness of coating one or both articles of the assembly with a material capable of preventing galvanic corrosion. The material coated on the articles was a fusion bonded, cured thermosetting polymeric material, Axalta Alesta 74550, which was applied to a thickness of about 0.0025 to 0.0035 inches after curing using a triboelectric method. All tests were conducted by fastening to magnesium and carbon fiber panels using M10 fasteners (bolts) with 10 microns of Dipzol NZ-200 alkaline plating. The tests included accelerated corrosion testing according to General Motors Global Engineering Standard Test Procedure GMW17026, "Accelerated Corrosion Laboratory Testing for Galvanic Corrosion Mechanisms" (Corrosion Test), tension loss testing and physical measurements to determine the suitability of the coating in relation to the mechanical requirements of the assembly.
[0093] The corrosion test was conducted using bolts mounted on sample panels (test pieces) of magnesium and carbon fiber. Each bolt on each test piece was coated with a fused cured thermosetting polymer material, and one control bolt on each test piece was not coated. The test pieces were placed on a plastic grid in a stainless steel chamber and subjected to direct spraying of a solution of 3% salt, 3% fire clay, and 94% water for 2 minutes every 3 hours at a temperature of 66°C (about 150.8°F). The spray was applied at a rate of about 2.5 liters (L) per minute per nozzle. The test piece had an initial thickness of about 3 millimeters (mm) before being exposed to the spray solution.
[0094] The corrosion test simulated exposure of the magnesium coupons to 1, 2, 3, 4, 5 and 8-9 years by subjecting the coupons to spraying for 5 days (1 year simulation), 10 days (2 years simulation), 15 days (3 years simulation), through 35 days (8-9 years simulation). The test was suspended after 35 days (8-9 years simulation) and the nuts securing the control bolts corroded through the magnesium coupons. Photos showing the visual results of the test are provided at Figures 9A-9G Among them, Fig. 9A The unexposed or prior to testing coated and uncoated bolts are shown on the left and right sides of the photograph, respectively, and, Figure 9B-9G Bolts after 1, 2, 3, 4, 5 and 8-9 years of simulated exposure are shown. It is clear from the photographs that after 35 days (8-9 years simulated), the magnesium coupons with coated bolts in the corrosion test chamber showed almost no signs of corrosion, while the coupons on which the uncoated bolts were mounted showed extreme corrosion and, as mentioned above, required that the test be suspended due to failure of the coupon (magnesium) material as a result of the coupon contacting the untreated nut on the back of the coupon. In this case, galvanic corrosion occurred in the magnesium coupons, as magnesium is more active or lower potential than steel and therefore acts as an anode in the galvanic reaction.
[0095] Fig.10 is a photograph showing a coupon after exposure to a simulated 15-year magnesium coupon. It can be easily seen that in the 15-year simulation test, the area of the coupon around the thermoset-coated bolts showed essentially no pitting, while the area of the coupon around the uncoated bolts showed strong pitting, and penetrating pitting was found (penetrating the 3 mm coupon thickness).
[0096] During the 35-day simulated test pause, the coupons with uncoated bolts had pitting as thorough as the coupons that had undergone the 15-year simulated test (pitting of about 3 mm), while the coupons with coated bolts had pitting less than about 0.089 mm, or less than about 3% of the pitting of the uncoated bolts.
[0097] Similar corrosion tests were conducted using undamaged and damaged, uncoated and coated bolts mounted to carbon fiber sample panels. The corrosion tests simulated exposure of magnesium coupons to 1, 2, 3, 4, 5, 10, 11, 12, 13, 14 and 15 years by subjecting the coupons to spray for 5 days (1 year simulation), 10 days (2 year simulation), 15 days (3 year simulation), through 65 days (15 year simulation). In the damaged bolt test, 1 kg (about 2.2 pounds) of bolts were placed in a hopper mounted on top of a 150 mm (about 6 inches) pipe, about 1 meter (39 inches) high. A trap door at the bottom of the hopper was opened to allow the bolts to fall into a (about 39 inches) non-metallic collection box. The drop process was repeated three times before the bolts were removed for testing.
[0098] Figures 11A-11L Photographs showing the visual results of the undamaged bolt test are provided, where Fig.11A The left and right sides of the photographs show the unexposed or pre-test coated and uncoated bolts, respectively, while Figures 11B-11L Bolts are shown after 1, 2, 3, 4, 5, 10, 11, 12, 13, 14 and 15 years of simulated exposure. Again, it is easy to see from the photos that the coated bolts on the carbon fiber panels show significantly less corrosion after 65 days in the corrosion test chamber (15 years simulation), while the uncoated bolts on the carbon fiber panels show extreme corrosion. Inspection of the photos (and especially Fig.11L ) showed that the coated bolts exhibited limited spread of surface staining to the carbon fiber panel to which they were mounted, while the uncoated bolts exhibited what appeared to be significant structural degradation and significant spread to the carbon fiber panel.
[0099] Figures 12A-12L Photographs showing the visualization of the damaged bolt test are provided, where Fig. 12A The left and right sides of the photographs show the unexposed or pre-test coated and uncoated bolts, respectively, while Figures 12B-12L Bolts are shown after 1, 2, 3, 4, 5, 10, 11, 12, 13, 14 and 15 years of simulated exposure. Again, it is easy to see from the photos that the coated bolts on the carbon fiber panels show significantly less corrosion after 65 days in the corrosion test chamber (15 years simulation), while the uncoated bolts on the carbon fiber panels show extreme corrosion. Inspection of the photos (and especially Figure 12L ) showed that the coated bolts exhibited limited spread of surface staining to the carbon fiber panel to which they were mounted, while the uncoated bolts exhibited what appeared to be significant structural degradation and significant spread to the carbon fiber panel.
[0100] In the case of the bolt in the carbon fiber coupon, it must be remembered that the galvanic corrosion occurs in the steel bolt and not in the carbon fiber coupon, since the steel is more active or has a lower potential than the carbon fiber and therefore acts as the anode in the galvanic reaction.
[0101] Understandably, because the bolts, rather than the coupons, were subject to galvanic corrosion, no weight loss measurements were made on the coupons. Figure 12L Inspection of the samples in 2009 showed that while the uncoated bolts had significant structural degradation and significant diffusion to the carbon fiber panel, the coated bolts exhibited limited diffusion of surface stains to the carbon fiber panel to which they were mounted.
[0102] Tension loss tests were also conducted to determine whether the coating caused an unacceptably increased tension loss in the coated bolts compared to uncoated bolts (control) and bolts coated with nylon 11 powder coating. Uncoated M-10 bolts (control), bolts coated with the thermosetting coating according to the present invention, and bolts coated with nylon 11 were placed in a 19 mm thick steel block. Galvanized steel washers were placed between the bolt heads, and 10 mm steel nuts were screwed on the threads of the bolts to secure the bolts to the block. The bolts were tightened to a torque of 45-55 N-m. The assembly including all bolts was heated to a temperature of 125° C. (about 257° F.) for 800 hours. A Dakota Ultrasonics MINI-MAX bolt tension monitor was installed on each bolt to ultrasonically determine the tension loss in the bolts. The thermosetting coating was applied to the bolts to a thickness of about 0.0025 inches to 0.0035 inches.
[0103] The uncoated bolts (control) exhibited a tension loss of about 20%, the bolts coated with the thermosetting coating according to the present invention exhibited a tension loss of about 25%, and the bolts coated with nylon 11 exhibited a tension loss of about 33% to 65%. Inspection of the test data showed that the tension loss of the bolts coated with the thermosetting coating according to the present invention exhibited an acceptably lower tension loss than the control bolts, while the bolts coated with nylon 11 exhibited an unacceptably high tension loss.
[0104] Thermal cycling tests of the tension loss of uncoated bolts (control) and bolts coated with the thermosetting coating according to the present invention and bolts coated with nylon 11 powder coating were also implemented, wherein the bolts were thermally cycled between -40°C and 80°C (about -40°F to 176°F). The bolts were thermally cycled for 13 cycles at a temperature between -40°C and 80°C and maintained at the temperature for 3 hours. The control bolts showed a tension loss of about 18.6%, the bolts with nylon 11 powder coating showed a tension loss of about 33.3% to 42.5%, and the bolts coated with the thermosetting coating showed a tension loss of between about 4.7% and 14.5%, showing no negative effect of the thermosetting coating on the tension loss in the thermal cycle.
[0105] Bolts coated with the thermosetting coating according to the present invention also exhibit a uniform and undisturbed coating. The coating thickness applied was about 0.63 mm (about 0.0021 inches) to about 0.89 mm (about 0.0029 inches) and was uniform when applied to a drive head having a recessed head such as a hexagonal wrench or The coating is also applied sufficiently along the threads so that the coating is present at the threaded engagement and has been found not to interfere with the securing of the bolt to the internally threaded member. Advantageously, the thermosetting coating has been found not to interfere with magnetism and therefore, the use of magnetic drivers and driver tips and magnetically securing bolts are not affected. A depiction of the uniformity and thickness of the coating on the bolt is shown in Figure 3 middle.
[0106] The bolts were also tested for coefficient of friction, which is the friction exhibited when the bolt is tightened to a component. The coefficient of friction is a dimensionless value, but corresponds to the force that must be applied to properly tighten or torque a bolt to a certain value. The coefficient of friction required to drive a bolt is about 0.10 to 0.16. The coefficient of friction of the coated bolts was adjusted to approximately this range by using a lubricant.
[0107] The description of these methods is exemplary only. In certain embodiments, the method may include additional combinations or substitutions of some or all of the above steps. In addition, in view of the beneficial effects of the present invention, additional and alternative suitable variants, forms and components for the method will be recognized by those skilled in the art. In addition, any component or feature of the above-mentioned article and / or assembly can be produced by the embodiment of the method, and any step or action described in relation to the article and / or assembly can be incorporated into the embodiment of the method.
[0108] As used herein, those skilled in the art will understand "about," "approximately," "substantially," and "significantly," which may vary to some extent in the context of use. As used herein, the terms "comprising" and "including" should be interpreted as having the same meaning as "containing" and "comprising," which are both "open" transitional terms that do not limit a claim to only the elements immediately following such terms. The term "consisting of," which is encompassed by the term "comprising," is to be interpreted as a "closed" transitional term that limits a claim to only the elements immediately following such terms. The term "consisting essentially of," which is encompassed by the term "comprising," should be interpreted as a "partially closed" transitional term that allows additional elements immediately following such terms, but only if such additional elements do not materially affect the basic and novel characteristics of the claim.
[0109] Those skilled in the art will further understand that relative directional terms, such as side, up, down, rearward, forward, etc., are only used for illustrative purposes and are not intended to limit the scope of protection of the present invention.
[0110] All patents involved in the present invention are hereby incorporated by reference into this document, whether or not explicitly cited in the text disclosed in the present invention. In the present invention, the word "one" or "an" should be understood to include the singular and the plural. On the contrary, any reference to a plural item includes the singular where appropriate.
[0111] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.
Claims
1. A method for preventing corrosion of a corrosion-prone component in a two-component system, characterized in that: The first component and the second component of the two-component system have surfaces facing each other, and the two components have different anodic indices, and the method includes: applying a coating material on a surface of the first component, the coating material being a thermosetting material, the surface of the first component including at least a portion of a threaded portion of the first component; curing the coating material on the surface of the first component; bringing the surface of the first component coated with the coating material into contact with and fixing the surface of the second component; Wherein, at least one of the first component and the second component shows almost no corrosion after a 15-year simulation test after being exposed to a corrosive environment specified in standard GMW17026.
2. The method according to claim 1, characterized in that: After exposure to the corrosive environment specified in standard GMW17026, both the first component and the second component showed almost no corrosion after a 15-year simulation test.
3. The method according to claim 1, characterized in that The method further comprises: reversibly connecting the first component and the second component to contact and secure the surface of the first component with the surface of the second component to form a releasable joint; The first component and the second component are heated to a predetermined temperature and maintained for a predetermined time after the two components are connected.
4. The method according to claim 3, characterized in that: The predetermined temperature is approximately 257°F, and the predetermined time is approximately 800 hours.
5. The method according to claim 1, characterized in that The method further comprises: threading the first component and the second component so that the surface of the first component contacts and is fixed with the surface of the second component to form a threaded joint; applying a predetermined torque to one of the first component and the second component relative to the other; After the threaded connection, heating the first component and the second component to a predetermined temperature and maintaining the temperature for a predetermined time; A tension loss of the threaded joint is measured after heating, wherein the tension loss of the threaded joint does not exceed about 25%.
6. The method according to claim 5, characterized in that The predetermined torque is approximately 45-55 N-m.
7. The method according to claim 6, characterized in that The predetermined temperature is approximately 257°F, and the predetermined time is approximately 800 hours.
8. The method according to claim 5, characterized in that The method further comprises: After the first component and the second component are threadedly connected, subjecting the first component and the second component to a thermal cycle from about -40°F to 176°F for about 13 cycles and maintaining the temperature for 3 hours; Wherein, the tension loss of the threaded joint does not exceed about 15%.
9. The method according to claim 1, characterized in that: The cured coating material has a uniform thickness of greater than 63.5 microns (0.0025 inches).
10. The method according to claim 9, characterized in that The cured coating material had a uniform thickness of 63.5 microns (0.0025 inches) to 88.9 microns (0.0035 inches).
11. The method according to claim 1, characterized in that: The cured coating material had a uniform thickness of 38.1 microns (0.0015 inches) to 88.9 microns (0.0035 inches).
12. The method according to claim 1, characterized in that The coating material is an epoxy material that is cross-linked during the coating process to form a cross-linked epoxy coating, and optionally: wherein the epoxy material is a fusion bonded epoxy material; or The epoxy material includes a curing agent, including one or more amines, anhydrides, acids, phenols, alcohols and thiols.
13. The method according to claim 12, characterized in that The epoxy material cures in about thirty seconds or less at a temperature of about 204.4 to 232.2 degrees Celsius (400 to 450 degrees Fahrenheit) to form the cross-linked epoxy coating.
14. The method according to claim 1, characterized in that The coating material includes a first coating material and a second coating material, and applying the coating material further includes: applying the first coating material; completely curing the first coating material to form a first cured layer; The second coating material is then applied over the first solidified layer.
15. The method according to claim 1, characterized in that The first component is a steel bolt and the second component is formed of a metal having a smaller anodic index.
16. The method according to claim 15, characterized in that The second component is formed of magnesium and the cured coating material is present on a head of the steel bolt; wherein when installed on a magnesium coupon, the magnesium coupon exhibits less than about 3% pitting under test procedure GMW17026 after a 15-year simulation test compared to an identical uncoated steel bolt.
17. The method according to claim 1, characterized in that Also included is heating the first component to a temperature of 125° C. for 800 hours, after which the first component exhibits no more than about 25% loss in tension.
18. The method according to claim 1, characterized in that The first component is a steel bolt including a head, and applying the coating material further comprises applying the coating material on a bottom of the head of the steel bolt.
19. The method according to claim 18, characterized in that Applying the coating material further includes applying the coating material on the head of the steel bolt.
